(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
We present calcareous nannofossil biostratigraphy and abundances for the Upper Pliensbachian-Lower Toarcian interval, including the Toarcian Oceanic Anoxic Event (T-OAE), represented by the Fish Level at Colle di Sogno (N Italy). In addition to biohorizons identifying NJT 5 and NJT 6 nannofossil zones, the first occurrences of C. superbus and D. striatus constrain the onset and the end of the T-OAE, respectively. We propose the last occurrence of M. jansae as additional event to approximate the end of the T-OAE at lower latitudes. Quantitative data highlight the “Schizosphaerella decline” marking the Pliensbachian/Toarcian boundary and the “Schizosphaerella crisis” at the onset of the T-OAE as supplementary biohorizons. S. punctulata and M. jansae constitute most of the micrite in the interval below the Fish Level, which is marked by an increase in abundance of small coccoliths remaining abundant in the overlying interval, with limited contributions of S. punctulata, while M. jansae disappears. Principal Component Analysis implemented nannofossil paleoecological and paleoenvironmental reconstructions. The latest Pliensbachian was characterized by stable oligotrophic conditions favourable to calcification at low pCO2 levels promoting the proliferation of deep-dwelling and highly-calcified S. punctulata. During the earliest Toarcian an initial pulse of continental run-off introduced terrigenous material favouring the intermediate-dweller M. jansae and the low-salinity adapted Calyculus. Higher nutrient concentrations and ocean acidification magnified during the T-OAE, stimulatying mesotrophic low-calcified coccolith-producers and suppressing k-strategist deep- to intermediate-dwellers. After the T-OAE, partial recovery of calcareous nannoplankton indicates still perturbed conditions. Ecosystem modifications anticipated the T-OAE of 1 million years with species origination and major changes in assemblages.